(untitled) (Revista Nacional de Odontología, 2017)
Introduction: The knowledgment of the mandibular region anatomy is fundamental for the performance of surgical interventions due to the neighborly relations between dental and osseous structures. The objectives of this work were to determine the path of the mandibular canal as a true conduit to the mental foramen in dry jaws, to establish the relation frequency between the inferior third molar with the conduit and to record the complications that occured during the eruption of the inferior third molar, before and after the surgical treatment, by sex and age. Methodology: 50 dry mandibular bones were used, silicon with barium sulfate added, orthodontic wire, drypoint dividers, milimetered ruler and radiographic films. Sagittal and frontal cuttings were performed to obtain base distances, alveolar ridge and tooth-conduit. Clinically, 100 patients of both sexes, 15 to 30 years were treated, and they were divided in two groups: patients with pre-treatment complications; patients with post-treatment complications. For the quantification and validation of data the percentual method and the Chi-square (x+) test were used, with a statistical significance of p<0.05. Results: It was determined that the lower mandibular canal is true in 80% of cases. In frontal cuttings, the conduit was located closert to the alveolar ridge. In sagittal cuttings, the distance between tooth and conduit were tiny. The data show higher frequency of complications in female patients, aged between 17 and 25 and with mesioangular and retained position of the tooth. The most obvious complications were: trismus pericoronaritis, nerve type pain and otitis. Conclution: Knowledge of the mandibular anatomy and of the neighborhood relations allow to work safely and efficiently, avoiding the risks that involves nerve complications associated with inferior alveolar nerve damage.